El gas natural licuado y su impacto en la circulación de la energía. Análisis multiescalar - Del Valle Guerrero, Ana Lía (2014)
In recent years there have been changes in global gas markets with different characteristics and scope, as the increasing use of liquefied natural gas (LNG); the growth of transport by ship in comparison with traditional gas pipelines; the introduction of unconventional resources such as shale gas and the presence of new actors. In this context, the general objective of this article is to analyze the changes in the energy flow, associated with the increasing transport of LNG by ship, in the context of the contemporary energy transition. Furthermore, as a specific objective we analyze the expansion of actors in the LNG market in the 2006-2013 period from a geo-economics point of view, that constitutes one of the central factors of analysis. Moreover, we analyze through a multiscale approach the geographical reconfiguration of the territory and the effects it produces on society, the environment and the territory. This approach is based on the idea that geographical scales represent complex and dynamic totalities where power relations are socially constructed through multiscale strategies by the actors involved.